2023
DOI: 10.3390/land12010167
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Spatial Discrete Heterogeneity of Housing Prices in Beijing, China, Based on Regionally Geographically Weighted Regression Affected by Education

Abstract: Spatial heterogeneity analysis of housing prices, in general, is crucial for maintaining high-quality economic development in China, especially in the post-COVID-19 pandemic context. Previous studies have attempted to explain the associated geographical evolution by studying the spatial non-stationary continuous heterogeneity; however, they ignored the spatial discrete heterogeneity caused by natural or policy factors, such as education, economy, and population. Therefore, in this study, we take Beijing as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…The GWR model was modified based on the traditional regression framework and can test spatial instability [40]. In order to quantify the spatial differentiation of the relationship between the ESs, we used the "GWModel" package in R 4.2 [41].…”
Section: • Gwr Modelmentioning
confidence: 99%
“…The GWR model was modified based on the traditional regression framework and can test spatial instability [40]. In order to quantify the spatial differentiation of the relationship between the ESs, we used the "GWModel" package in R 4.2 [41].…”
Section: • Gwr Modelmentioning
confidence: 99%
“…Jiang analyzed the leased price of houses in Beijing through the GTWR model and showed that the plot ratio, property cost, green rate, traffic density, public service facilities, and other quantities have a significant impact on the house rental price. Generally speaking, the housing leased prices in Beijing are not randomly distributed in space, there is a positive correlation, and the housing rental prices in neighboring areas have the nature of mutual influence [22]. This also indirectly indicates that improving the leased space of urban villages is conducive to the improvement of housing value and thus contributes to the benign development of the rental market in the surrounding areas.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%